PENERAPAN AJARAN WULANG REH DAN WEDATAMA UNTUK MENINGKATKAN KESEHATAN MENTAL REMAJA SMA NEGERI 1 BAMBANGLIPURO - Muhammad Iqbal Birsyada; Sigit Handoko; Latifah Putranti; Pradita Nindya Aryandha (Universitas PGRI Yogyakarta, 2025)
Today's teenagers face serious challenges in terms of mental health, especially due to social and academic pressures, as well as the negative influence of digital media. Lack of self-management is the root of various psychological problems such as stress, anxiety, and deviant behavior. This community service activity aims to improve the mental health of teenagers through the education of the noble values ​​contained in the teachings of Wulang Reh and Wedatama. This program was implemented at SMA Negeri 1 Bambanglipuro, targeting grade XII students, and involved stages of observation, focus group discussions, coordination with partners, and implementation of interactive education. The results of the activity showed an increase in students' understanding of the concepts of self-control, inner peace, and positive thinking. In addition, there was a change in students' attitudes in dealing with pressure and an increased awareness of the importance of local cultural values ​​as a foundation for character formation. This activity proves that a local wisdom-based approach can be an effective alternative in efforts to improve the mental health of teenagers in the school environment. Keywords: Adolescent Mental Health, Wulang Reh, Wedatama, Local Wisdom, Self-Management, Character Education